(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the concept of civil society and analyzes the role of spiritual and educational factors—particularly the teachings of Sufism—in its formation. It is substantiated that Sufi ideas serve as a significant factor in the development of a stable civil society by enhancing human spirituality and fostering virtues that ensure social harmony, such as tolerance, patience, and forgiveness. The article also explores the historical roots of Sufism, its influence on the moral and normative worldview of the Uzbek people, and its relevance in the moral upbringing of youth in the context of globalization. The author provides a scholarly and theoretical account of the role of religious and spiritual values—especially the constructive contribution of Sufi thought—in the establishment of a civil society.